A psychometric analysis of the adapted historical loss scale and historical loss associated symptoms scale among native Hawaiian adults - Antonio, Mapuana C. K.; Keaulana, Samantha; Ing, Claire Townsend; Williams, Madison; Dillard, Adrienne; Kekauoha, Bridget Puni; Kenney, Meghan; Marshall, Sarah Momilani; Cassel, Kevin; Abrigo, Scott; Kauhane, Michelle; Kaholokula, Joseph Keawe‘aimoku (Frontiers in Public Health, 2024)
Objectives: The Historical Loss Scale (HLS) and Historical Loss Associated Symptoms Scale (HLASS) are standardized measures that have been accepted and previously validated among North American Indigenous communities and allow researchers to measure the impact of Historical Loss. Evidence of the psychometric properties of this instrument have not been assessed for Native Hawaiians, the Indigenous peoples of Hawai‘i. The purpose of this study is to investigate the psychometric properties of the adapted HLS (aHLS) and HLASS for adults from multiple Hawaiian Homestead Communities throughout Hawai‘i. Methods: Data are based on cross-sectional surveys administered between 2014-2020. The final sample included 491 Native Hawaiian adults who were predominantly female (67.3%) and between the ages of 18 to 90 years, who were part of the larger study entitled the Hawaiian Homestead Health Survey. Factor analyses were conducted to determine the final model structures of each scale. Reliability and correlation matrices of items are also reported. Results: The final factor structure of the aHLS model suggested 3 factors: 1) General loss of culture or cultural loss, 2) Intergenerational loss, and 3) Distrust and destruction of traditional foods. The final HLASS model also suggested 3 factors: 1) Depression and Anger 2) Shame and Anxiety, and 3) Re-experiencing, fear, and avoidance. Conclusions: These findings have implications for future research, practice, and education that explores the role of Historical Loss and associated symptoms in Native Hawaiians and Indigenous communities at large. In particular, measuring historical loss and associated symptoms in Hawaiian Homestead communities paves the way for quantitative assessments of historical trauma and healing in these communities.